2022
DOI: 10.3390/foods11244027
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between the Egg Yolk Flavor of Indigenous 2 Breeds and Commercial Laying Hens Based on Sensory Evaluation, Artificial Sensors, and GC-MS

Abstract: The focus of this study was to compare the yolk flavor of eggs from laying hens of Chinese indigenous and commercial, based on detection of volatile compounds, fatty acids, and texture characteristics determination, using sensory evaluation, artificial sensors (electronic nose (E-nose), electronic tongue (E-tongue)), and gas chromatography-mass spectrometry (GC-MS). A total of 405 laying hens (Hy-Line Brown (n = 135), Xueyu White (n = 135), and Xinyang Blue (n = 135)) were used for the study, and 540 eggs (180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The results showed that the discrimination of SEY under three heat treatments could be effectively facilitated by employing an E-tongue. A previous study also revealed that different sensors of the E-tongue can significantly differentiate between different varieties of egg yolk flavors with distinct separation distances [39].…”
Section: E-tongue Analysismentioning
confidence: 92%
“…The results showed that the discrimination of SEY under three heat treatments could be effectively facilitated by employing an E-tongue. A previous study also revealed that different sensors of the E-tongue can significantly differentiate between different varieties of egg yolk flavors with distinct separation distances [39].…”
Section: E-tongue Analysismentioning
confidence: 92%
“…Literature study on the comparison between the egg yolk flavor of indigenous breeds and commercial laying hens based on sensory evaluation, artificial sensors, and GC-MS reported significant breed differences for sensory attributes of egg yolk, but the differences in egg weight among the breeds were not significant (Gao et al,2022). Furthermore, the search results suggest that non-significant results are common in studies on egg production and egg quality in laying hens.…”
Section: Average Egg Weightmentioning
confidence: 93%
“…Few works show the use of more than one technological tool, despite the fact that the combination of these tools allows for better management of different types of resources (scientific personnel, economic resources, time, raw materials). However, Huang et al (2023) , Chen et al (2023) , Gao et al (2022) and Martínez-Velasco et al (2022) made use of more than one technological tool. This article consolidates information on some technological tools reported in the literature for sensory analysis in various food matrices.…”
Section: Introductionmentioning
confidence: 99%